124k views
21 votes
Solve by substitution. Show each step of your work.

4x + y = 12


6x + 2y = 18


Please help!!!

User Bohemian
by
5.4k points

2 Answers

8 votes

5x + y = 15

y = -5x + 15

Substituting y= -5x+15 from first equation into second equation:

3x + 2y = 16

3x + 2ยท(-5x + 15) = 16

3x - 10x + 30 = 16

-7x + 30 = 16

7x = 30 - 16 = 14

x = 2

Substituting x=2 into the first equation:

5x + y = 15

5(2) + y = 15

10 + y = 15

y = 15 - 10

y = 5

So your final answers are x=2 and y=5.

User Andriy Ivaneyko
by
6.7k points
5 votes

Answer:

x = 3, y = 0

Explanation:

First we find a variable to cancel out. Y will be easiest.

Multiply that equation by -2 to create
-8x-2y = -24

Now we can cancel y out and solve for x.

add the variables together to make 10x = 30

x = 3

Now that we have x, we can plug it in for either equation to find y.


4(3) + y = 12

y = 0

User Kadir Erdem Demir
by
5.3k points